The Role of Spike Protein Mutations in the Infectious Power of SARS-COV-2 Variants: A Molecular Interaction Perspective (2022)
ABSTRACT: Specific S477N, N501Y, K417N, K417T, E484K mutations in the receptor binding domain (RBD) of the spike protein in the wild type SARS-COV-2 virus have resulted, among others, in the following variants: B.1.160 (20A or EU2, first reported in continental Europe), B1.1.7 (α or 20I501Y.V1, first reported in the United Kingdom), B.1.351 (β or 20H/501Y.V2, first reported in South Africa), B.1.1.28.1 (γ or P.1 or 20J/501Y.V3, first reported in Brazil), and B.1.1.28.2 (ζ, or P.2 or 20B/S484K, also first reported in Brazil). From the analysis of a set of bonding descriptors firmly rooted in the formalism of quantum mechanics, including Natural Bond Orbitals (NBO), Quantum Theory of Atoms In Molecules (QTAIM) and highly correlated energies within the Domain Based Local Pair Natural Orbital Coupled Cluster Method (DLPNO-CCSD(T)), and from a set of compute electronic spectral patterns with environmental effects, we show that the new variants improve their ability to recognize available sites to either hydrogen bond or to form salt bridges with residues in the ACE2 receptor of the host cells. This results in significantly improved initial virus···cell molecular recognition and attachment at the microscopic level, which trigger the infectious cycle.